Welfare Effects of Public Service Broadcasting in a Free-to-Air TV Market - Gernot Sieg; Jula Rothbauer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
A welfare-maximizing Public Service Broadcaster (PSB) broadcasts both information-type and show-type content if (i) the information consumption of TV viewers generates external benefits for society by improving the ability of voters to control politicians and (ii) the marginal external benefits of information consumption diminish as the information possessed by voters increases. We analyze a two-sided free-to-air TV market with two differentiated private channels and a commercial-free PSB. Welfare depends on the efficiency of the PSB, the external benefits of voter information, and lost rents from the advertising market. Welfare can be higher without a PSB.
Keywords: L82; D72; L32; 330